Ambient Task With Stimulus-Response Compatibility Concept for Guiding Alzheimer’s Actions - N. W. Basharudin; Ku Azir K.N.F; P. Ehkan; A. M. Khairuddin (Institute of Advanced Engineering and Science, 2018)
Alzheimer is one of the diseases that can cause the patient to act in different and unpredictable ways. This disease destroys memory and thinking skills and, eventually, the ability to carry out the simplest tasks. Advanced in technology actually can help them be more independent doing their routines. Hence, this study was conducted to investigate the relationship between stimulus-response compatibility (SRC) and ambient intelligent elements for Alzheimer’s patients. The aim of this study is to obtain a strong answer on how ambient elements (stimulus) such as ambient colours, lights and pictures can assist Alzheimer’ patients in daily living activities. For this reason, we developed a flashcard game based on ambient colours and pictures to achieve two objectives which are (i) to test the ambient’s factors that highly effect the responses of Alzheimer’s patients and (ii) to observe the response towards the given instructions. This experiment has been tested to 10 participants with mild-stage of Alzheimer’s disease. The findings of this experiment show that the patient response more towards ambient colours compared to the ambient pictures. 90% of respondents capable to complete the task correctly and quickly based on ambient colours. In addition, the experiment proved that the participants have no difficulty in order to understand the instructions given to them for completing the tasks smoothly.